PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH MENENGAH - Diyah Nuraini Mahmudah; Yayah Kurniawati (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2026)
This study aims to analyze the strengthening of the Pancasila Student Profile through Civics Education learning at SMK Islam Sudirman Ungaran, Semarang Regency. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of Civics Education teachers and students at SMK Islam Sudirman Ungaran. Data were collected through observation, interviews, and documentation. Data analysis employed an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that the strengthening of the Pancasila Student Profile through Civics Education learning is carried out through three main stages: planning, implementation, and efforts to address learning challenges. In the planning stage, teachers integrate the dimensions of the Pancasila Student Profile into learning tools such as teaching modules, learning objectives, and contextual learning activities. During the implementation stage, teachers apply participatory learning methods such as group discussions, case studies, and presentations that encourage students to develop cooperation, critical thinking, and respect for diversity. However, several challenges were identified, including limited instructional time, differences in students’ levels of understanding, and limited variation in teaching methods. Therefore, innovative learning strategies and a supportive school environment are required to optimize the strengthening of the Pancasila Student Profile.